Weitere Aethiopica der Staatsbibliothek zu Berlin, Preußischer Kulturbesitz - Six, Veronika (Aethiopica, 2006)
New acquisition of Ethiopian manuscripts in the "Staatsbibliothek zu Berlin, Preußischer Kulturbesitz": each manuscript with a with short description as well as a description of the picture story, which was enclosed.